Leveraging machine learning essentiality predictions and chemogenomic interactions to identify antifungal targets - Ci Fu (Nature Portfolio, 2021)
The analysis of essential genes in pathogens can be used to discover potential antimicrobial targets. Here, the authors use a machine learning model and chemogenomic analyses to generate genome-wide gene essentiality predictions for the fungal pathogen Candida albicans, define the function of three uncharacterized essential genes, and identify the target of a new antifungal compound.